HUBUNGAN ANTARA KOMPETENSI PROFESIONAL GURU DAN MEDIA PEMBELAJARAN DENGAN KEMANDIRIAN SISWA KELAS V DALAM PEMBELAJARAN ONLINE - Syafniarti, Syafniarti; Zulfitria, Zulfitria; Winata, Widia (Universitas Muhammadiyah Jakarta, 2022)
ABSTRACTThe purpose of this study was to analyze: 1) The relationship between teacher professional competence and student learning independence in online learning, 2) The relationship between learning media and student learning independence in online learning, and 3) The relationship between teacher professional competence and learning media with learning independence. students in online learning. This study uses a quantitative approach with a survey method. The population of this study were all elementary school students in West Cakung Sub-district, Cakung District, East Jakarta. The research sample was 100 fifth grade students from 4 elementary schools, namely: SDN Cakung Barat 01, SDN Cakung Barat 06, SDN Cakung Barat 15, and SDN Pulogebang 03. The results showed that; 1) There is a positive and significant relationship between Teacher Professional Competence and Student Independence in Online Learning, 2) There is a positive and significant relationship between Learning Media and Student Independence in Online Learning, and 3) There is a positive relationship between Teacher Professional Competence and Learning Media together with Student Independence in Online Learning.ABSTRAKTujuan penelitian ini adalah untuk menganalisis: 1) Hubungan antara kompetensi profesional guru dengan kemandirian belajar siswa dalam pembelajaran online, 2) Hubungan antara media pembelajaran dengan kemandirian belajar siswa dalam pembelajaran online, dan 3) Hubungan antara kompetensi profesional guru dan media pembelajaran dengan kemandirian belajar siswa dalam pembelajaran online. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi penelitian ini adalah seluruh siswa SDN se-Kelurahan Cakung Barat, Kecamatan Cakung, Jakarta Timur. Adapun sampel penelitian adalah 100 siswa kelas V dari 4 SDN yaitu: SDN Cakung Barat 01, SDN Cakung Barat 06, SDN Cakung Barat 15, dan SDN Pulogebang 03. Hasil penelitian menunjukkan bahwa; 1) Terdapat hubungan yang positif dan signifikan antara Kompetensi Profesional Guru dengan Kemandirian Siswa Dalam Pembelajaran Online, 2) Terdapat hubungan yang positif dan signifikan antara Media Pembelajaran dengan Kemandirian Siswa Dalam Pembelajaran Online, dan 3) Terdapat hubungan positif Kompetensi Profesional Guru dan Media Pembelajaran secara bersama-sama dengan Kemandirian Siswa Dalam Pembelajaran Online.